A ratiometric electrochemical sensor for lead ions based on bismuth film coated porous silicon nanoparticles. (6th February 2020) - Yu, Lei; Cui, Xin; Yue, Xiangguo; Yu, Zhenguo
Abstract : A ratiometric electrochemical sensor for the detection of lead ions was developed based on porous silicon nanoparticles with in situ plated bismuth to improve the accuracy and reliability. Abstract : A simple and effective ratiometric electrochemical sensor has been developed for the detection of lead ions. This sensor was based on porous silicon nanoparticles with in situ deposition of a bismuth film. Porous silicon was prepared via electrochemical etching of silicon wafers in solution containing hydrofluoric acid, ethanol and hydrogen peroxide. The porous silicon samples were characterized by scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, and Fourier transform infrared spectroscopy. A modified electrode was applied to detect Pb(ii ) in water samples by differential pulse anodic stripping voltammetry. By using Bi(iii ) as an internal reference standard, the current ratio of Pb(ii ) to Bi(iii ) offers higher stability and reproducibility than the current of Pb(ii ) itself. The calibration curve in the ratiometric current signal exhibited a linear response from 0.2 to 100 μg L −1, with a limit of detection of 0.09 μg L −1 to Pb(ii ), enhancing the sensitivity by a factor of 1.9 in comparison with non-ratiometric methods.